First Detection of SARS-CoV-2 B.1.617.2 (Delta) Variant of Concern in a Symptomatic Cat in Spain - Sandra Barroso-Arévalo; Sandra Barroso-Arévalo; Lidia Sánchez-Morales; Lidia Sánchez-Morales; Marta Pérez-Sancho; Marta Pérez-Sancho; Lucas Domínguez; Lucas Domínguez; José M. Sánchez-Vizcaíno; José M. Sánchez-Vizcaíno (Frontiers in Veterinary Science, 2022)
Natural and experimental SARS-CoV-2 infection in pets has been widely evidenced since the beginning of the COVID-19 pandemic. Among the numerous affected animals, cats are one of the most susceptible species. However, little is known about viral pathogenicity and transmissibility in the case of variants of concern (VOCs) in animal hosts, such as the B.1.617.2 (Delta) variant first detected in India. Here, we have identified the B.1.617.2 (Delta) VOC in a cat living with a COVID-19 positive owner. The animal presented mild symptoms (sneezing) and a high viral load was detected in the oropharyngeal swab, suggesting that an active infection was occurring in the upper respiratory tract of the cat. Transmission from the owner to the cat occurred despite the human being fully vaccinated against SARS-CoV-2. This study documents the first detection of B.1.165.2 VOC in a cat in Spain and emphasizes the importance of performing active surveillance and genomic investigation on infected animals.